Odour emissions from anaerobically co-digested biosolids: Identification of volatile organic and sulfur compounds - Guerrero, Thais N.; Le-Minh, Nhat; Fisher, Ruth M.; Prata, Ademir A. [UNESP]; Stuetz, Richard M. (Elsevier, 2025)
Anaerobic co-digestion is emerging as an option for wastewater biosolids management. Variations in treatment parameters can impact odour emissions and, in turn, odour nuisance reduces community acceptance and alternatives for beneficial reuse of biosolids via land application. This study assessed odour emissions from digested sludge and biosolids resulting from the anaerobic co-digestion of wastewater sludge with beverage rejects (beer and cola) and food wastes. The sludge and biosolids were obtained from two parallel pilot plant digesters operating with primary sludge obtained directly from a wastewater treatment plant, in which five different campaigns of co-digestates were studied – beer reject (10 %), cola reject (10 %), food waste A (10 %), food waste A (20 %), and food waste B (10 %). Gas chromatography–sulfur chemiluminescence detector (GC–SCD) and gas chromatography–mass spectrometry (GC–MS) were used for detection of volatile sulfur compounds (VSCs) and volatile organic compounds (VOCs) respectively. Sensory assessments were conducted using an odour detection port (ODP) connected to the GC–MS with two panellists. Variations in concentration, frequency, and intensity, were observed between the different campaigns. Hydrogen sulfide was the predominant VSC. However, other VSCs such as methyl mercaptan, dimethyl sulfide, dimethyl disulfide, and dimethyl trisulfide were also identified as important odorants. Sixteen of the VOCs were identified as potential odorants, with toluene and 2-butanone having the highest VOCs concentrations and p-cresol having the highest odour activity values. Despite limited attention in the literature, VOCs contributed to the overall odour perception of biosolids and sludge gaseous emissions. This study highlighted the unpredictability of the impact of anaerobic co-digestion on odour emissions, emphasizing the need for thorough examination before introduction of co-substrates. Further research is recommended to understand the impact of different co-substrate feeds on odorant emissions.
Keywords: Anaerobic co-digestion; Beneficial reuse; Beverage reject; Biosolids; Co-digestate; Food waste; Gaseous emissions; Land application; Odour emissions; Wastewater sludge